Aquarium Water Quality Monitoring Based On Internet Of Things - Bima Setya Kusumaraga; Syamsudduha Syahrorini; Dwi Hadidjaja; Izza Anshory (Procedia of Engineering and Life Science, 2021)
Guppy fish is one type of ornamental fish that is widely kept in aquariums. Water temperature, water pH, and water turbidity are important factors for the life and development of guppy fish in an aquarium. The ideal water conditions for guppy fish in the aquarium are 23-27oC, a pH value of 6.5-7.5, and a water turbidity level of 0-25 NTU. To maintain ideal water conditions, research is needed to keep the aquarium water conditions stable. The research was conducted by experimenting using the NodeMCU platform as a microcontroller and the DS18B20 temperature sensor for sensing water temperature, a pH sensor 4502C, and a TDS sensor for sensing water turbidity. Testing is done by detecting the condition of the aquarium water with all sensors simultaneously to find out the water conditions in real time. The test results show that the tool designed is able to maintain water temperature at 23-27 oC, maintain pH values at 6.5-7.5, and water turbidity at 0-25 NTU. Thus the tool is able to maintain the ideal aquarium water quality for guppies.